DERMATOGLYPHIC PATTERN IN RELATION TO ABO, RH BLOOD GROUP AMONG MEDICAL STUDENTS (Journal of Forensic Medicine & Toxicology, 2023)
Dermatoglyphics provides a scientific method for identification of an individual and it is constant and same till demise. Fingerprint evidence is undoubtedly play an important role during identification of criminals, biometric, aadhar card, etc. In Modern Era, fingerprints becomes an effective method of identification and in present study an attempt has been made to analyse their correlation with gender, ABO & Rh blood group of an individual. The present study was conducted among the medical students of Mahatma Gandhi Memorial Medical College, Indore, India. Total 194 students were selected (107 male and 87 female) within age group of 19-28 years. Fingerprint patterns (loops, whorls, and arches) was taken using the INK method and blood data were collected. On conclusion, 38.65% of subjects belong to B blood group followed by O, A and AB where 94.32% subject having Rh-positive. Loops were higher in both male & female. Among the subject of different blood groups, blood group ‘A’ showed highest loops (Rh positive 62.19%), blood group ‘O’ showed highest Whorls (Rh positive 45.88% and Arches were least common ranging from 9.32% (in “B” positives) to 5.29% (in “AB” positives). All such parameters may help in using fingerprints as an important factor in Gender, ABO & Rh blood group determination which enhancing the authenticity of finger-prints in detection of crime and criminals.
Keywords: ABO blood group; Arches; Dermatoglyphics; Loops; Rh blood group; Whorls